2022
DOI: 10.2478/pomr-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Characteristics of a Low-Emission Gas Turbine Combustion Chamber Operating on a Mixture of Natural Gas and Hydrogen

Abstract: This article is devoted to the investigation of the characteristics of a low-emission gas turbine combustion chamber, which can be used in Floating Production, Storage and Offloading (FPSO) vessels and operates on a mixture of natural gas and hydrogen. A new approach is proposed for modelling the processes of burning out a mixture of natural gas with hydrogen under preliminary mixing conditions in gaseous fuel with an oxidizer in the channels of radial-axial swirlers of flame tubes. The proposed kinetic hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To solve this problem, Vakili et al [166] developed an energy management framework to reduce air emissions in shipbuilding. In addition, optimizing the ship design [167][168][169], using advanced techniques and applying post-treatment methods for SOx and NOx reduction [170][171][172][173][174][175][176][177], using low or free-carbon fuels (hydrogen, ammonia) [178][179][180][181][182][183][184][185], and/or developing methods for recovering the waste heat from large marine diesel engines [186][187][188][189], using renewable energy and energy storage technologies in ships, port, and vehicles in port [85,[190][191][192] could also be potential solutions to reduce pollutant emission from maritime and port actions. Although the above studies propose to solve this pollution by different methods, they are all towards sustainability for the environment, especially a specific environment such as seaports.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this problem, Vakili et al [166] developed an energy management framework to reduce air emissions in shipbuilding. In addition, optimizing the ship design [167][168][169], using advanced techniques and applying post-treatment methods for SOx and NOx reduction [170][171][172][173][174][175][176][177], using low or free-carbon fuels (hydrogen, ammonia) [178][179][180][181][182][183][184][185], and/or developing methods for recovering the waste heat from large marine diesel engines [186][187][188][189], using renewable energy and energy storage technologies in ships, port, and vehicles in port [85,[190][191][192] could also be potential solutions to reduce pollutant emission from maritime and port actions. Although the above studies propose to solve this pollution by different methods, they are all towards sustainability for the environment, especially a specific environment such as seaports.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the use of alternative fuels or fuel management could be considered an efficient solution for GL, since these types of fuel could reduce carbon emissions and hence reduce environmental pollution [124][125] [126]. As reported in the literature, a large number of alternative fuel types could be used for transportation means aiming to reduce pollutant emissions into the environment, such as hydrogen [127][128][129] [130], biogas [131][132], biodiesel [133] [134] [135], LPG, LNG or CNG [136][137] [138], alcohol [139] [140], ether [141][142], bio-oil [143][144], and ammonia [145].…”
Section: Use Of Alternative Fuels and Renewable Energymentioning
confidence: 99%
“…HFGT typically exhibits greater power output compared to HFC, albeit at a lower level of efficiency [15]. Moreover, the interchangeability of HFGT and natural gas turbine is good, and natural gas turbine can realize hydrogen combustion through burner transformation [16].…”
Section: Introductionmentioning
confidence: 99%
“…HFGT typically exhibits greater power output compared to HFC, albeit at a lower level of efficiency [15]. Moreover, the interchangeability of HFGT and natural gas turbine is good, and natural gas turbine can realize hydrogen combustion through burner transformation [16]. Indeed, the development of HFGT is rooted in the existing hydrogen‐blended combustion technology of gas turbines, offering unmistakable advantages [17].…”
Section: Introductionmentioning
confidence: 99%